2019
DOI: 10.3389/fpsyg.2018.02678
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Emotion Decoding From Facial Action Sets

Abstract: Researchers have theoretically proposed that humans decode other individuals' emotions or elementary cognitive appraisals from particular sets of facial action units (AUs). However, only a few empirical studies have systematically tested the relationships between the decoding of emotions/appraisals and sets of AUs, and the results are mixed. Furthermore, the previous studies relied on facial expressions of actors and no study used spontaneous and dynamic facial expressions in naturalistic settings. We investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Studying the impact of context on emotion perception is essential, as presenting participants with face stimuli lacking contextual information creates an experimental setting that has low ecological validity. In real life, observers process contextual information to accurately interpret the meaning of emotion displays, especially given that displays observed in naturalistic emotional situations are nuanced and include subtleties (Hyniewska et al, 2019) which make them challenging to univocally categorize per se (Hess et al, 1997;Sato et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studying the impact of context on emotion perception is essential, as presenting participants with face stimuli lacking contextual information creates an experimental setting that has low ecological validity. In real life, observers process contextual information to accurately interpret the meaning of emotion displays, especially given that displays observed in naturalistic emotional situations are nuanced and include subtleties (Hyniewska et al, 2019) which make them challenging to univocally categorize per se (Hess et al, 1997;Sato et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Durán et al showed in their meta-analysis on the coherence between facial expressions and emotional experiences that prototypical whole facial patterns were not coherent with the emotional experiences of the expressers, whereas there was a small coherence between their emotional experiences and individual facial components [ 19 ]. Moreover, Hyniewska et al illustrated how each facial component could be associated with the perceivers’ specific decoded emotions [ 20 ]. Furthermore, Reschke et al showed that physical changes of the mouth expressing disgust induced different emotional perceptions [ 21 ]; the disgust expression with an open mouth, compared to the disgust expression with a closed mouth, can lead to different inferences according to the type of contextual information available, such as posture-scene stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that “felt,” but not “false” smiles [as defined by Ekman and Friesen ( 1982 )] correlated strongly positively with a “in good humor” scale in agent ratings and both types of judges' ratings, but only weakly so with self-ratings. The video material collected by Scherer and Ceschi in this field study was used by Hyniewska et al ( 2018 ) to study the emotion antecedent appraisals (see Scherer, 2001 ) and the resulting emotions of the voyagers claiming lost baggage inferred by judges on the basis of the facial expressions. The videos were annotated with the FACS system and stepwise regression was used to identify the AUs predicting specific inferences.…”
Section: Introductionmentioning
confidence: 99%